Awarding for the Great Exhibition of Indonesian Painting and Jakarta Biennale in 1974-1989 - Atmadiredja, Genardi; Adriati, Ira (Mudra Jurnal Seni Budaya, 2020)
In the history of the development of post-independence Indonesian art, the national award was initiated by Dewan Kesenian Jakarta (The Jakarta Arts Council) through Pameran Besar Seni Lukis Indonesia (PBSLI) or The Great Exhibition of Indonesian Painting in 1974. PBSLI awarded the best work through the judging mechanism. The dynamics occurred after the award gave rise to different perceptions and opinions about how good works of art at the time were. This study examines the impact of PBSLI and Biennale Jakarta, the event’s name was altered in 1982, in terms of artist selection process, judging, social situation, and opinions in the Indonesian arts during 1974-1989. This study uses the qualitative research method with a historical approach. Data were collected through archival research and in-depth interviews. By implementing Artistic Field of Bourdieu, the study demonstrates that the results of PBSLI and Biennale Jakarta bestowed artists a symbolic capital which characterized the taste of arts at that time.